Suicide Attepmt Follow-Up Training - Davis, Maureen (Canadian Journal of Counselling and Psychotherapy, 2011)
The community of Prince George, located in the Northern Interior of British Columbia, has limited resources to assist suicide attempters although it has one of the highest suicide rates in the province. The community also has difficulty attracting and retaining professional counsellors. Consequently, those who attempt suicide are often left to deal with their problems alone. The Prince George Suicide Attempt Follow-Up Program is designed to train paraprofessionals to address the critical needs of suicide attempters. An evaluation of this project demonstrated the project's success in the preparation of paraprofessionals to work with suicide attempters while also highlighting some essential components of support and evaluation that must be met before the program can be fully implemented.